Cinema and backlighting: on the threshold of repression of Argentine media culture - Serelle, Márcio (Pontifícia Universidade Católica de São Paulo, 2014)
This paper examines the backlighting technique used in Argentine movies (mainly Valentín, Kamchatka, and The Secret in Their Eyes), seen as a kind of narrative composition in which events related to dictatorships and other forms of repression operate in the dark, but strongly affect the fate of the characters. Starting from a brief overview of the internationalization of the Argentine film industry, which, as early as the mid-1980s,had already articulated conventional dramatic structures and political denunciation, this study analyzes how part of the cinema of this century represents the violence of authoritarian states. Be it through imaginative investment, metalanguage, or allegory, these narratives renounce graphic images of the violence of repressive apparatuses and create dramaturgical compositions of highly effective communication. Thus, this work discusses the reflective capacity of these films as it pertains to the relationship between the fictional, mediatic and social contexts. Este artigo busca examinar em filmes argentinos (notadamente Valentín, Kamchatka e O segredo dos seus olhos) o procedimento da contraluz, entendido como um modo de composição narrativa em que eventos relacionados a ditaduras e outras formas de repressão movem-se no escuro, porém atuando agudamente sobre a trajetória das personagens.A partir de uma breve recuperação do movimento de internacionalização da cinematografia argentina, que, já em meados de 1980, articula estruturas dramáticas convencionaise denúncia política, pretende-se analisar o modo como parte do cinema deste século representa a violência de estados autoritários. Seja pelo investimento imaginativo, pela metalinguagem ou pela alegoria, essas narrativas renunciam às imagens explícitas da violência dos aparatos repressores e engendram dramaturgias de grande eficácia comunicacional. Coloca-se, assim, em discussão, a capacidade reflexiva desses filmes no que se refere às relações entre o ficcional, o midiático e o social.